Aldehyde deformylation by nonheme metal complexes – a mechanistic study - Nag, Sayanta Sekhar (My University, 2021)
The emission of greenhouse gases and particulate matter has profoundly impacted climate change by unsettling the earth's radiation balance. Fossil fuel burning is the primary reason for increasing the concentration of greenhouse gases and aerosol particles. Many of the so-called first-world countries are reducing their fossil fuel consumption substantially. In economically progressing countries like India, there is a lot of complexity depending on those alternatives. The crude oil refinery industry also produced a wide variety of commodity products for everyday uses. Biomass has particular interest among scientists because it can reduce the dependencies on fossil feedstock by generating both fuels and the necessary chemicals in a net carbon neutral biosynthetic pathway. In a petroleum refinery industry, apart from the extensive use of fuels, hydrocarbons are the primary raw material for producing various commodity products. The prospect of using the biosynthesis of hydrocarbon as an alternative to the crude oil refinery systems accelerated the fascination towards mechanistic enzymology.
Sastri, Chivukula V
Keywords: Bioinorganic Chemistry; Reaction Mechanism; Deformylation